OSSEOUS PLATE ALKALINE-PHOSPHATASE IS ANCHORED BY GPI - Pizauro, J. M.; Ciancaglini, P.; Leone, F. A. (Associação Brasileira de Divulgação Científica (ABRADIC), 1994)
Alkaline phosphatase activity was released up to 100% from the membrane by using 0.1 U of phosphatidylinositol-specific phospholipase C from B. thuringiensis. The Mr of solubilized enzyme was 145,000 by Sephacryl S-300 gel filtration and 66,000 by SDS-PAGE, suggesting a dimeric structure. Solubilization of the membrane-bound enzyme with phospholipase C did not destroy its ability to hydrolyze p-nitrophenyl phosphate (PNPP) (264.3 mu mol min(-1) mg(-1)), ATP (42.0 mu mol min(-1) mg(-1)) and pyrophosphate (28.4 mu mol min(-1) mg(-1)). The hydrolysis of ATP and PNPP by solubilized enzyme exhibited ''Michaelian'' kinetics with K-0.5 = 70 and 979 mu M, respectively. For pyrophosphate, K-0.5 was 128 mu M and site-site interactions were observed (n = 1.4). Magnesium ions were stimulatory (K-d = 1.5 mM) but zinc ions were powerful non-competitive inhibitors (K-d = 6.2 mu M) of solubilized enzyme. Treatment of solubilized alkaline phosphatase with Chellex 100 reduced the original PNPPase activity to 5%. Cobalt (K-0.5 = 10.1 mu M), magnesium (K-0.5 = 29.5 mu M) and manganese ions (K-0.5 = 5 mu M) restored the activity of the apoenzyme with positive cooperativity, suggesting that phosphatidylinositol-specific phospholipase C-solubilized alkaline phosphatase is a metalloenzyme. The stimulation of the apoenzyme by calcium ions (K-0.5 = 653 mu M) was lower than that observed for the other ions (26%) and exhibited site-site interactions (n = 0.7). Zinc ions had no effect on the apoenzyme of the solubilized enzyme.
Keywords: PHOSPHATIDYLINOSITOL; ANCHOR; Alkaline phosphatase; Osseous plate; P-NITROPHENYL PHOSPHATE